The value dimension of media practice in Algeria through media legislation An analytical study of the organic media law 2012 - أمال توهامي (International Journal of Social Communication, 2022)
The current study aimed to reveal the value dimension of media practice in Algeria through media legislation, whereas we analyzed the organic law of media 2012 using the descriptive survey method and the documentary analysis tool. we had as a conclusion that this law aims to regulate media practice in all its forms (written, radio, television and electronic one) within the framework of our value system derived from the Islamic religion, the culture and identity of the community, where its rules included a set of values (such as integrity, transparency, objectivity, respect, freedom, truth, authenticity, non-racism, non-violence, etc) It has explicitly stipulated that practicing media work must be within the framework of this system and that it should work to preserve and promote it and every violation of these values will have its punishment.